TRANSPORT SYSTEM IN RELATION TO EXTERNAL ENVIRONMENT (Perner's Contacts, 2011)
This article deals with influencing of transport demand on external macroeconomical environment from viewpoint of transport services demand forming with regard to capability possibilities of transport systém, next viewpoint is represented also by possibilities of competition development on transport market including all relevant important aspects with aim of transport services higher quality assurance.